Provision and protection of the rights of indigenous peoples of the North as a function of public authorities - N. Silantieva (Правоприменение, 2017)
The subject. The article describes the main problems of protection of the rights and freedomsof indigenous peoples as one of the most vulnerable groups of residents in a modernstate. The author emphasizes the relevance of the study, based on increased attention tothe preservation of the peoples of the North, especially by the international community.The purpose. The author dwells particularly on the legal protection of the rights of indigenouspeoples of the North, both on the global and national levels. The main tasks and functionsof state authorities on support and protection legal status of the indigenous Northernpeople are discussed.The methodology. General scientific methods (systemic, structural, formal logical) and special(technical, legal, statistical) methods are used.Results and scope of it’s application. After the analysis the national legislation the authoridentifies the shortcomings that impede the efficient activities of state authorities in thisdirection and comes to the conclusion that the Russian normative legal base, regulating theactivity of indigenous peoples of the North and protection of their rights, does not fullymeet modern requirements and existing needs. Among the major remedy options the authorcites a number of provisions which may be laid in the basis of the revised state policy.Conclusions. The Russian Federation has not used the full potential of the tools to preservethe culture and identity of peoples of the North, which allows to simulate and to conductfurther research to improve the quality of life of the peoples of the Russian North.